Strategi Pengasuhan dalam Perspektif Hadist dalam Menghadapi Krisis di Setiap Fase Perkembangan - Zainuddin, Kurniati; Ahmad, La Ode Ismail; Ngampo, Muhammad Ali (NANAEKE: Indonesian Journal on Early Childhood Education, 2024)
Parenting is an important and complex task. One of the goals of parenting is to support the child through every crisis at every stage of his development. Various approaches have been used to raise children so that children become complete human beings. The purpose of this paper is to examine parenting strategies from a hadith perspective, as a guide in setting goals and parenting strategies in supporting children through developmental crises according to Erickson's theory of socioemotional development. The results of this study show that various strategies such as aqiqah, giving a good name, open communication patterns, and providing life skills to children are strategies taught by the Prophet (saw) to parents to optimize children's growth and development